MONITORING OF INVASION ADVENTIVE PLANTS IN MULTIPLE PLANTS - Дыченко, Оксана; Ласло, Оксана (SWorldJournal, 2020)
Adventive invasive plant species that can be naturalized in perennial walnut plantations are analyzed, including: Solidago сanadensis L, Solidago Serotinoides A., Bidens frondosa L., Erechtites hieraciifolius, Impatiens parviflora DC., Echinocystis lobata